1998
DOI: 10.1002/(sici)1099-0488(19980415)36:5<789::aid-polb6>3.3.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

A new conception on the toughness of nylon 6/silica nanocomposite prepared via in situ polymerization

Abstract: A novel method, in situ polymerization, was used for the preparation of nylon 6/silica nanocomposites, and the mechanical properties of the nanocomposites were examined. The results showed that the tensile strength, elongation at break, and impact strength of silica-modified nanocomposites exhibited a tendency of up and down with the silica content increasing, while those of silica-unmodified nanocomposites decreased gradually. It also exhibited that the mechanical properties of silica-modified nanocomposites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
115
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(124 citation statements)
references
References 3 publications
6
115
0
3
Order By: Relevance
“…Indeed, the filler/matrix adhesion, filler dimensions, dispersion and content play important roles in the final mechanical properties of the composites. [9] The effects of the above-mentioned parameters on the polymer mechanical properties were carefully reviewed by Fu et al [10], who concluded that the composite strength and toughness are mainly affected by the particle/matrix adhesion, expanding a former study by Ou et al [11]. Moreover, regarding the effect on Young's modulus, a critical particle size was determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the filler/matrix adhesion, filler dimensions, dispersion and content play important roles in the final mechanical properties of the composites. [9] The effects of the above-mentioned parameters on the polymer mechanical properties were carefully reviewed by Fu et al [10], who concluded that the composite strength and toughness are mainly affected by the particle/matrix adhesion, expanding a former study by Ou et al [11]. Moreover, regarding the effect on Young's modulus, a critical particle size was determined.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, one of the main problems related to nanocomposites is the effective dispersion of the NPs in the polymer matrix [12]. For instance, Ou and coworker showed that when the content of silica in Nylon 6 is above 5 wt%, the particle aggregation occurs, leading to a decrement of the composite tensile strength and elongation at break [11]. In order to overcome this typical drawback, the authors have optimized a procedure, only recently called reactive suspension method (RS method), which is based on the in situ synthesis of oxide NPs in polymeric matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their high adsorption energies and high surface-to-volume ratio, nanoparticles in composites offer a range of new materials with useful combinations of properties. silica 4,8 (modified or unmodified) and in situ polymerization of the inorganic fillers, where silica sol is added to caprolactam and mixed into a reactor. 9 The most prominent physical effect of fillers is the stiffening or modulus increase in the composites.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the ratio is obtained from the linear region of the stress-strain curve [5,17]. A number of reports [18][19][20][21][22][23][24][25][26][27] [5]. In this report, the Young moduli were calculated based on the values of stress and strain bounded between 1 and 5 % strain of the tensile data points.…”
Section: Resultsmentioning
confidence: 99%
“…2 shows the dependence of Young's modulus on filler concentration of the composites. As seen, the behaviour is contrary to trend that is familiar with conventionally filled polymer composites [18][19][20][21][22][23][24][25][26][27]. Instead of observing the usual consistent increases in modulus, result shows an S-type monotonic decrease in Young's modulus with increasing particle loading.…”
Section: Resultsmentioning
confidence: 99%